Application of starch-degradation bacteria in cigar tobacco leaf fermentation: effects on starch degradation, microbial communities and metabolic pathways - Yuming Yin; Xueru Song; Yonghe Cui; Jilai Zhang; Kejian Fu; Qi Zhou; Yuxing Feng; Jiakui Huang; Chenglei Hu; Yishu Deng; Youbo Su (Frontiers in Microbiology)
ObjectiveThis study aims to explore the effects of inoculating starch-degrading strains on the starch content and microbial metabolic pathways of cigar tobacco leaves.MethodBy isolating and screening starch-degradation bacteria from the surface of Dominican tobacco leaves at the end of fermentation and applying them to the fermentation process of “Yunxue NO. 39” cigar tobacco leaves. The study systematically analyzed the starch content, microbial diversity and community structure, starch metabolic enzyme profiles and key metabolic pathway changes in tobacco leaves fermented for 18 and 35 days, integrating physicochemical composition, non-targeted metabolomics and metagenomics.ResultThe results indicated that both strains Bacillus pumilus and Bacillus velezensis (DX and BLS) exhibited strong starch degradation capabilities. Inoculation with starch-degradation bacteria significantly enhanced the diversity of the microbial community, enriched functional microbial community (such as Bacillus, Acinetobacter, Staphylococcus and Aspergillus), markedly influenced the composition of tobacco leaf metabolites and optimized the micro-environment of tobacco leaf fermentation. Metagenomic analysis revealed that the dynamic changes of starch metabolic enzymes (such as α-amylase, β-amylase and glucoamylase) during the fermentation process were closely related to the succession of the microbial community, with Bacillus and Aspergillus promoting starch degradation through synergistic interactions. KEGG pathway analysis revealed that starch metabolism is primarily accomplished through four core pathways: starch and sucrose metabolism, amino sugar and nucleotide sugar metabolism, glycolysis/gluconeogenesis and mycolic acid biosynthesis. This study provides a theoretical basis for the quality improvement of cigar tobacco leaves and confirms the potential application value of starch-degradation bacteria in tobacco fermentation.